Prosodic Effects of Focus and Constituency in Mandarin and in English - Meghan Clayards; Michael Wagner; Wei Zhang (Laboratory Phonology)
The prosody of an utterance encodes multiple types of information simultaneously, including information status of constituents—for example, by modulations in prosodic prominence to encode focus—and information about syntactic constituent structure—by modulations of prosodic phrasing. According to many prosodic theories, however, focus and constituent structure interact with each in their effects on prominence and phrasing respectively. Focus early in an utterance is sometimes assumed to preempt the realization of tonal events later in the utterance, thus neutralizing syntactically-motivated phrasing distinctions. Other accounts assume that focus and constituent structure exert their effects on prominence and phrasing in an additive way. The current study compares English and Mandarin and investigates to what extent the correlates of focus and constituency interact with each other in shaping the prosody in production. The results show that syntax-induced phrasing distinctions are still encoded post-focally in both languages, providing new evidence for the view that different functions can be encoded orthogonally in prosody. Additionally, we found that while the two languages realize phrasing in roughly same way, they differ in their acoustic realization of focus. Mandarin relies more on F0 modulation than English, and Mandarin lexical tones interact with focus realization.